The Faces of the Second Amendment Outside the Home: History versus Ahistorical Standards of Review - Charles, Patrick J. (2012)
This article disagrees that the courts need to reinvent or recast the Second Amendment outside the home to reflect its “fundamental” status as recognized in Heller and McDonald. The history of public arms regulation already provides significant guideposts for the courts to adjudicate the right to “keep and bear arms” in public. To accomplish this, it requires placing history in context and not letting mythical interpretations or historical assumptions to permeate.Thus, this article begins by decoding the public carrying of arms as the founding generation would have understood it. It provides substantiating historical evidence that counters the mythical meanings of the Statute of Northampton, and proves that the Statute did not solely seek to regulate a particular conduct with the intent to terrify, but the activity of carrying arms among the public concourse. It was the act of carrying arms itself that was deemed to terrify the people, for it was thought to be uncommon and unsafe to go armed in a well-regulated society. Such conduct ran counter to the idea of government authority and the police power.In addition to this showing, this article weighs the historical approach against others, particularly libertarian balancing and the importation of First Amendment jurisprudence into the Second. To apply either of these latter approaches would be unprecedented in the pantheons of arms regulation history and American jurisprudence altogether. Not once did the founding generation conflate public arms carrying with a presumption of liberty or prior restraint. Instead, arms regulation was premised on what was in the interest of the public good